Diseño y desarrollo de un sistema de gestion de seguridad y salud ocupacional ohsas 18001:2007 para una empresa importadora, distribuidora y comercializadora de productos agroquimicos - Posada Sánchez, Pablo Rómulo (2010)
This thesis has as a main objective the implementation of OHSAS 18001: 2007 for a company importing, repackaging, formulator, distributor and marketer of agricultural chemicals located in the city of Guayaquil on Via Daule. The company employs 74 people and due to the type of business has in its inventory products that are of high risk because they are flammable, corrosive, toxic and explosive with a high level of danger to personnel and the environment. The company has three classes of pesticide products: fungicides, insecticides and herbicides as well as products for water treatment. With the implementation seeks to establish a Safety Management System and Occupational Health to eliminate, minimize and in some cases anticipate the risks of the business in which the company operates, using techniques and procedures in the Standard OHSAS 18001: 2007. On the basis of which the company does not have a security system suitable for handling and use of chemicals with which it works.